INTEGRATING LOCAL WISDOM: INNOVATIVE ASSESSMENT INSTRUMENT OF CRITICAL THINKING SKILLS IN SCIENCE LEARNING - Dini, Naffa Afkarina Izzata; Kuswanto, Heru (JURNAL EDUSCIENCE, 2025)
Purpose- This research aims to develop a valid and reliable instrument for measuring students' critical thinking skills in learning integrated with local wisdom.Methodology- The research addresses the need for culturally relevant assessment tools that align with modern educational goals and promote the appreciation of local heritage. Employing the ADDIE development model, the study follows a systematic approach encompassing five stages: analysis, design, development, implementation, and evaluation. The sample consisted of 56 seventh-grade students from MTSN 2 Ponorogo.Findings- The research results show that data collection involved validity and reliability tests to ensure the instrument's effectiveness. Expert evaluations yielded an average validity score of 96%, categorizing the instrument as "very feasible." Reliability analysis using the Quest program revealed that nine out of ten question items achieved INFIT MNSQ scores within the ideal range of 0.71 to 1.40, demonstrating their suitability and alignment with established measurement criteria. However, one item fell outside this range, indicating a need for further refinement.Significance- The conclusion of this research shows the instrument's potential to assess critical thinking skills while accurately incorporating cultural values. Integrating local wisdom, specifically through educational practices that connect learning to traditional cultural elements, enhances students' critical thinking abilities and fosters an appreciation for cultural heritage. This research is significant for educators, curriculum developers, and policymakers seeking to balance modern pedagogical practices with cultural preservation.